E-Wallet Literacy Scale Development and Validation - Kotni, V. V. Devi Prasad (Indian Journal of Finance, 2024)
Purpose : Many people used cashless payment methods, mostly e-wallets, during the COVID-19 pandemic. This incentivized numerous financial institutions and banks to offer e-wallets to their clientele, facilitating digital financial transactions. Given the importance of assessing e-wallet literacy, a carefully designed and thoroughly examined scale is needed. This study aimed to create and provide a fully validated and tested scale for assessing the literacy levels of e-wallet users. Methodology : This study created and validated the scale using the scientific and statistical procedures for scale development. Stakeholders, including academics, researchers, and e-wallet users (656), participated in this study at different phases. To create and validate the e-wallet literacy measure, the study employed panel interviews, primary data gathering, exploratory factor analysis, and confirmatory factor analysis (using AMOS). Findings : Credit payment transactions (CPT), bill payment transactions (BTT), investment transactions (IT), money transfer transactions (FTT), purchase transactions (PT), and method of payment (MOP) are the six components that the study revealed, which can be used to quantify e-wallet literacy. With 26 scale items, these six constructs were created. Practical Implications : The measure can be employed by e-wallet service providers to evaluate the degree of e-wallet proficiency within their intended customer base. Campaigns to raise consumer awareness can be tailored to these literacy levels to promote more use of e-wallets. Government authorities and policymakers acknowledged E-wallets as essential tools for achieving financial inclusion. Originality : Unlike prior research on e-wallets, the current work constructed a scale to examine the literacy levels of users concerning e-wallets.